Serial Within-Session Improvements in Ankle Dorsiflexion During Clinical Interventions Including Mobilization-With-Movement and A Novel Manipulation Intervention - A Case Series - Mohsen Abassi; Rod Whiteley (North American Sports Medicine Institute, 2021)
# Background Persisting reductions in ankle dorsiflexion range of motion are commonly encountered clinically and seen to be associated with adverse outcomes after ankle and other lower extremity injuries. Accordingly improving identified deficits is a common goal for rehabilitation; however, little data exists documenting any improvement related to interventions in these patients. # Purpose To document the change in dorsiflexion range of motion after stretching and mobilization-with-movement and exercise and a novel manipulation intervention in a population of injured athletes. # Design Case series in 38 consecutive injured athletes with persisting reductions in ankle dorsiflexion range of motion (42 "stiff" ankles, 34 uninjured) in an outpatient sports physiotherapy clinic. # Method During a single treatment session, two baseline measurements of weight-bearing dorsiflexion were taken at the start of the session to establish reliability and minimum detectable change, and then the same measures were performed after stretching and a mobilization-with-movement intervention, and again after clinical exercise and a novel manipulation which was applied on both ankles. # Results Excellent reliability was demonstrated (ICC~2,1~\>0.93, MDC=3.5°) for the dorsiflexion measure. Statistically significant (p\<0.01), but clinically meaningless improvements were seen after stretching and the mobilization-with-movement intervention on the injured and uninjured legs (1.9° and 1.4° respectively) with greater improvements seen after exercise and the subsequent manipulation (6.9° and 4.7°). # Conclusions The relatively simple clinical exercise and manipulation intervention program was associated improvement in dorsiflexion range of motion in this cohort with persisting ankle stiffness. The interventions described largely restored range of motion consistent with baseline levels of the uninjured ankles. Improvements were also seen in the uninjured ankles following intervention.